(untitled) (Journal of Engineering, 2010)
Three revolutions characterize the age of information: Information Revolution,Technology Revolution and Media Revolution. These revolutions developed and interacted with each other in an amazing way. Way to an extent that it becomes a title to our contemporary architecture. These revolutions changed people‟s thoughts, behaviors, and traditions. The effect of technology on the urban structure generally and the urban space specifically changed the physical structure of these spaces as a necessary result to the change of intellectual structure in community. The information revolution changed a lot of the common urban space„s characteristics and concepts as well as an extreme change in concepts related to the space. The new thought concentrated on the fact that information represents the tools for the interaction between man and his environment. The new electronic information and the improved digital media split the reality out of the realm of body, convert the experiments to the form of event and create a control of the virtual reality. The new space of this kind is called “Virtual Space”. This new space lies between the physical space and the mental space as it presents to the designers not only infinity image to the mental space but the sense of being in the physical space. The physicality of space is no more an important concept in architecture as a result to the emergence of new concepts of space with the effect of information technology. The new digital tools (computers) set free the dual concepts of space in human civilizations. The power of structure and the imitation of the digital media released all types of unlimited imagination. The research aims to explain the concept of (space) in the language of today (the technological language) and clarify the meaning of intelligent space as a result of the change in the concept of space in the age of Informational Technology Revolution .